Office 2016 for dummies - Wang, Wally (2016)
"Following alongside approachable, plain-English explanations, you'll quickly discover how to type, format text, and design documents in Word; navigate and edit spreadsheets, create formulas, and analyze data in Excel; configure email, store contacts, organize tasks, and schedule your time with Outlook; create and edit well-designed and crowd-pleasing PowerPoint presentations; and design, edit, and modify an Access database. Even if the mere thought of working with Microsoft Office makes you nervous, this fun and friendly guide makes it easy" --
Introduction -- Part I: Getting Started with Office 2016 -- Part II: Working with Word -- Part III: Playing the Numbers with Excel -- Part IV: Making Presentations with PowerPoint -- Part V: Getting Organized with Outlook -- Part VI: Storing Stuff in Access -- Part VII: The Part of Tens -- Index.
Includes index.
Keywords: Microsoft Office; Microsoft Office; Business -- Computer programs